2017
DOI: 10.21608/epx.2017.11252
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of respirable particulates in two residential areas of Kuwait State during dusty and nondusty storms: A time-series comparative study

Abstract: Background: Kuwait State is branded by the recurrent dust storms and high pollution level. It has the highest dust concentration and surface temperature in Peninsula. The aim of the present study was to assess the respirable particulates during days with and without dust storms in two residential areas in Kuwait State. Materials and Methods:This time-series comparative study was accomplished during the period from 1 January 2013 to 31 December 2013. It was conducted by recording the local meteorological data i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…77 studies found which measured different pollutants indoor or/ and outdoors, where majority of these studies (59 studies) measured only outdoor pollutants (Abdul-Wahab et al, 1996, Al-Awadhi, 2016, Al-Awadhi, 2014, Al-Awadhi and Alshuaibi, 2013, Alet al, 2008a, Al-Dabbous and Kumar, 2014, Al-Dabbous and Kumar, 2015, Al-Dabbous et al, 2016, Aldaihani and Alenezi, 2017, Alenezi and Al-anezi, 2015, Al-Hurban and Al-Ostad, 2009, Alkandari and Moein, 2018, Alshammari, 2018, Al-Shammari, 2013, Bourasli, 2013, Bu-Olayan and Thomas, 2011, Bu-Olayan and Thomas, 2010b, Engelbrecht et al, 2009b, Kuśmierczyk-Michulec and Bourgouin, 2018, Li et al, 2020, Nasrallah et al, 2003, Yassin, 2011, Yassin et al, 2018a, Zaki et al, 2017.…”
Section: Non-epidemiological Studiesmentioning
confidence: 99%
“…77 studies found which measured different pollutants indoor or/ and outdoors, where majority of these studies (59 studies) measured only outdoor pollutants (Abdul-Wahab et al, 1996, Al-Awadhi, 2016, Al-Awadhi, 2014, Al-Awadhi and Alshuaibi, 2013, Alet al, 2008a, Al-Dabbous and Kumar, 2014, Al-Dabbous and Kumar, 2015, Al-Dabbous et al, 2016, Aldaihani and Alenezi, 2017, Alenezi and Al-anezi, 2015, Al-Hurban and Al-Ostad, 2009, Alkandari and Moein, 2018, Alshammari, 2018, Al-Shammari, 2013, Bourasli, 2013, Bu-Olayan and Thomas, 2011, Bu-Olayan and Thomas, 2010b, Engelbrecht et al, 2009b, Kuśmierczyk-Michulec and Bourgouin, 2018, Li et al, 2020, Nasrallah et al, 2003, Yassin, 2011, Yassin et al, 2018a, Zaki et al, 2017.…”
Section: Non-epidemiological Studiesmentioning
confidence: 99%